O programa Universidade para Todos (Prouni) e a expansão do ensino superior brasileiro - Basconi, Tatiane Cristina Fernandes [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
This dissertation is a reflection, taking as its starting point a problem: would the Program University for All (Prouni) have become a program that, in addition to the certification of the working youth was used by the State to supply the labor market with contingents of licensed teachers coming from the working class? Our hypothesis is that such inquiry proceeds and it is confirmed by the difficulty of the State to recruit teachers qualified to serve on the State Public Schools, considering that the conjuncture is of an initial formation devoid of content that provides the future teacher with a preparation for the critical understanding of reality and with prospects for acting for social changes, contributing for the precariousness of the teaching work. To undertake this task, the Prouni was chosen as object of study during the period between 2005 and 2013 and the established objectives were: 1) unveiling the constitutive mediations of the program, seeking to place it in the context of neoliberal educational policies that guided the expansion of access to higher education in Brazil, turning it into a big business. Thus, analyses of national and international documents and official data for analysis of the situation in which the expansion of higher education happened since the period of the military governments, were conducted, seeking to highlight the American influence on the University reform bill which promoted differentiation/diversification of the institutions and the privatized expansion as a way to tailor it to the bourgeois imperialist and national interests, materialized in the MEC-USAID agreement in the 1970s and in the guidelines of the World Bank since 1990, which require a minimum State model for social policies; 2) understanding the initial formation of the teachers and their class origin, as well as the impoverishment and precariousness of working conditions and contracts as evidence of the existence of a process of...
Keywords: ProUni (Programa); Educação e Estado - Brazil; Educação e Estado - Brasil; Ensino superior; Professores - Formação; Privatização na educação